Illness Costs Saved due to Changes of Ceramic Production Fuel in Bat Trang Village - Ha, Nguyen Thi Vinh; Yen, Luong Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 4, 2018)
The paper presents economic value of environmental benefit thanks to cleaner production, via the reduction of cost of illness when fuel for production changed from coal to gas in Bat Trang ceramic village, Hanoi in 2008-2018. The results show that the saved cost is 40 billion dongs per year. On individual level, the average gain is 3.5 million dongs/year. This savings is enough for building new ovens in 3 years. In addition, the producers get higher profit due to fuel savings and better product quality and higher production volume. This is a good evidence that cleaner production brings both economic and social gains.